BT, fostering the change in the British telecom industry - Coelho, João Maria Lérias Machado De Noronha (2021)
This equity research aims to study British Telecom PLC to assess the viability of investing in the British telecommunications industry. After determining the company's main pillars to be followed, one will understand the key value drivers of the company's business: fiber rollout and spectrum acquisition. Once observing the specific customer-facing units where such improvements will be testified, one will determine main costing and investment strategies, not forfeiting the pension plan analysis. To terminate, one can get acquainted with the cash flow policy while resorting to the main value creation drivers. Relying on a Discounted Cash Flow analysis to forecast a recommendation, one complements the analysis by resorting to a scenario analysis to understand potential market variations.